철도터널 유지관리 계측센서의 손망실율 연구 - 우종태; Woo, Jong-Tae (한국재난정보학회 논문집, 14(3), 2018)
Purpose: This paper investigates and analyzes the loss and damage ratio of maintenance monitoring sensor in metropolitan and high speed railroad tunnel in Korea and abroad. Method: After 5~6 years from the installation, the maintenance monitoring sensor on metropolitan transit tunnels showed the loss and damage ratio from 14.2% to 14.8% in Seoul metro line no. 5, 6, 7, 9, and 13.9% in UK channel tunnel. Based on the result, 15% is thought to be a proper set for the elapsed years, which is 5 years from the installation. Results: The maintenance monitoring sensor on high speed railroad tunnels showed the loss and damage ratio of 60.9% in Ho-Nam high speed railroad on 1 stage after 3 ~ 5 years from the installation, which was approximately 4 times as high as that of Seoul metro line no. 5, 6, 7, 9. Conclusion: Kyung-Bu high speed railroad on 2 stage, after 8~10 years from the installation, showed the loss and damage ratio of 66.8%. Based on the result, it can be inferred that the loss and damage ratio increases drastically after 5~10 years from the installation. Therefore, it is necessary to study on the loss and damage ratio of long term elapsed years, especially more than 10 years from the installation. 연구목적: 본 연구는 국내와 국외의 도시 및 고속철도터널 유지관리 계측센서의 손망실 현황을 조사하고 분석을 실시하였다. 연구방법: 도시철도터널 유지관리 계측센서 설치 후 5년에서 6년의 손망실율은 서울 지하철5,6,7,9호선은 14.2%에서 14.8%, 영국의 Channel tunnel은 13.9%로 거의 유사하게 나타나 5년 경과연수에서는 15%로 설정하는 것이 타당한 것으로 판단된다. 연구결과: 고속철도터널 유지관리 계측센서 설치 후 3년에서 5년의 손망실율은 호남고속 철도1단계 에서 60.9%로 서울지하철5,6,7,9호선의 4배 이상 크게 나타났다. 결론: 8년에서 10년의 경부고속철도2단계에서는 66.8%로 나타나 5년에서 10년 사이에 급격하게 증가하므로 향후 10년 이상 장기간의 경과연수에 따른 계측항목별 손망실율 연구가 필요할 것으로 판단된다.